2012
DOI: 10.1111/j.1439-0388.2012.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between litters per sow per year sire breeding values and sire progeny means for farrowing rate, removal parity and lifetime born alive

Abstract: The objective of this study was to determine the relationship between individual sire estimated breeding values (EBV) for litters/sow/year (LSY) and sire progeny means for farrowing rate (FR), removal parity and lifetime born alive (LTBA). Genetic parameters and breeding values were estimated using ASREML. The heritability estimate for LSY was 0.11. When all sires with 10 or more daughters with records were included in the analysis, Spearman rank correlations between the sire's LSY EBV and the sires' daughter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…The overall mean and the means by farm obtained in this study for LBA are lower than the means reported by Abell et al (2013) in USA, in Japan, and Engblom et al (2007) in Sweden (53.8, 52.5, and 52.7 piglets, respectively). However, they are higher than values (34.9 and 38.5 piglets) reported in the USA by Hoge and Bates (2011) and Nikkilä et al (2013)).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The overall mean and the means by farm obtained in this study for LBA are lower than the means reported by Abell et al (2013) in USA, in Japan, and Engblom et al (2007) in Sweden (53.8, 52.5, and 52.7 piglets, respectively). However, they are higher than values (34.9 and 38.5 piglets) reported in the USA by Hoge and Bates (2011) and Nikkilä et al (2013)).…”
Section: Discussioncontrasting
confidence: 83%
“…1 and 2) by year may be due in part because it considers only sows that culled. Thus, the lower means observed in the last 2 years are due in part to the culling of low-parity young (1-3 farrowing) sows (Soltesz and Balogh 2013;Abell et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Four general methods were used to calculate accuracy: using prediction error variance (PEV) from the inverse left‐hand side (iLHS) and calculating the traditional accuracy (Forni et al., ), approximated accuracies (Misztal & Wiggans, ; Misztal et al., ), correlating predictions to the GEBV from the full data set (similar to Aguilar et al., ) and correlating predictions to the corrected phenotypes (Abell et al., ; Christensen et al., ; Lourenco et al., ). There were three separate implementations using the corrected phenotypes (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Much of the focus for GS has been placed on models and far less on the accompanying validation methods being used. Many articles use only one or maybe two methods and have ignored justification of the validation methods being used for accuracy comparisons between models (Abell, Mabry, Dekkers, & Stalder, ; Christensen, Madsen, Nielsen, Ostersen, & Su, ; Forni et al., ; Guo et al., ; Lourenco et al., ; Serão et al., ). In a review paper on GS by de los Campos, Hickey, Pong‐Wong, Daetwyler, and Calus (), accuracy validation methods were not thoroughly discussed, yet play a critical role to compare alternative breeding programmes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major components of litter index is lactation length (Abell et al, 2013). In a simplistic approach, farms that opt out for a higher weaning age of the piglets are expected to have a lower litter index.…”
Section: Sow-related Performance Parametersmentioning
confidence: 99%